Assessment of Jamaica’s Climate Change Mitigation Potential and Implications for its Updated NDC : Sectoral Review - World Bank (World Bank, Washington, DC, 2021)
This report considers the opportunities based on domestic commitments already made for Jamaica to enhance the ambition of the mitigation commitments of its future Nationally Determined Contribution (NDC). It also identifies the adaptation co-benefits these opportunities might bring, which could provide an input into the qualitative narrative of the next NDC and specifies the additional technical work that will be needed to confirm these opportunities within a revised NDC.